Pengaruh Penerapan Nilai-Nilai Syariah dan Kualitas Pelayanan terhadap Kepuasan Nasabah (Studi Kasus: Bank Syariah Indonesia KCP Sumberrejo Bojonegoro) - Sutiya Lestari; Lailatul Nur Afifah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This study aims to test and analyze the effect of the application of Sharia values and service quality on customer satisfaction (study at Bank BSI KCP Bojonegoro Sumberrejo). The population of this study was customers of Bank BSI KCP Bojonegoro Sumberrejo, with a saturated sample of 30 respondents. The analytical methods used in this study are validity tests, reliability tests and multiple linear regression. The results showed that partially the variable application of Sharia values did not affect customer satisfaction. Meanwhile, partially the variable of service quality has a significant effect on customer satisfaction. And simultaneously the variables of the application of sharia values and the quality of service have a positive and significant effect on customer satisfaction